THE DEDICATORY INSCRIPTION OF THE STOA OF ATTALOS IN THE ATHENIAN AGORA PUBLIC PROPERTY, COMMERCIAL SPACE, AND HELLENISTIC KINGS. - Kaye, Noah (Hesperia)
Published here are two overlooked fragments of the dedicatory inscription of the Stoa of Attalos in the Athenian Agora (Agora I 6135). A substantial body of inscriptions documenting stoas and associated rooms bestowed as gifts by both royal and civic donors suggests a new reconstruction of the text, one which is supported by the incorporation of the new fragments. The epigraphical pairing of the building and the rooms elucidates the economic character of the stoa as gift and the impact of this form of euergetism on the polis. This clarification occasions a reconsideration of royal property rights in the urban environment, at issue in the case of Hellenistic Sardis and the Second Letter of Antiochos III to Sardis (SEG XXXIX 1285).